Pelatihan Alat Bantu Penyandang Disabilitas Sebagai Upaya Meningkatkan Kualitas Hidup di Desa Taman Ayu Kabupaten Lombok Barat - Wanadiatri, Halia; Juniawan, Alvin; Sabariah, Sabariah (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to improve the ability of people with disabilities to use disability aids as an effort to improve their quality of life. The implementation method of this activity included data collection, training, and evaluation. Partners of this activity included Foster Cadres and People with Disabilities in Taman Ayu Village, West Lombok Regency. The results of this community service activity showed that participants with disabilities had the ability to use aids consisting of wheelchairs, canes, and hearing aids. In addition, information was provided regarding the place and how to care for these aids. It is hope that with the ability to use these aids, the quality of life of people with disabilities will improve.